Prenatal Therapy Improves the Survival of Premature Infants with Congenital Chylothorax - Chia-Jung Lee; Po-Nien Tsao; Chien-Yi Chen; Wu-Shiun Hsieh; Jyun-you Liou; Hung-Chieh Chou (Pediatrics and Neonatology)
Chylothorax is a rare condition among neonates, although it is considered clinically significant, as it is difficult to manage in these patients. In addition, the course of chylothorax varies widely. Therefore, we aimed to elucidate the clinical features and effect of prenatal therapy on the prognosis of congenital chylothorax in neonates. Methods: We retrospectively reviewed the medical records of all infants with congenital chylothorax who were admitted to National Taiwan University Hospital, Taipei, Taiwan between January 2000 and December 2012. Their demographic characteristics, as well as their antenatal, perinatal, and postnatal information, were collected for our analysis of the mortality risk. Results: We found 29 infants who were diagnosed with congenital chylothorax during the study period. The median gestational age at birth was 34 weeks (range, 28–41 weeks), and 71% of the infants presented with hydrops fetalis. Most cases of congenital chylothorax were bilateral (bilateral: 86.2%, unilateral: 13.79%), and the overall survival rate was 59.6%. Among the cases with a prenatal diagnosis at ≤ 34 weeks of gestation, infants who received prenatal therapy had a significantly higher survival rate, compared to infants who did not receive prenatal therapy (76.9% vs. 11%, respectively; p = 0.008). Conclusion: We found that infants whose chylothorax was diagnosed ≤ 34 weeks of gestation, and who subsequently received prenatal therapy, experienced a better perinatal condition and exhibited improved postnatal outcomes.